EFFECT Of NITROGEN FERTILIZER TYPES AND ZINC FOLIAR APPLICATION ON GROWTH AND YEILD OF SNAKE CUCUMBER (Cucumis Melo var. Flexuosus) - & ALgailany, Mnagd (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was carried out in the spring season of 2016 in sedimentary soil (silty clay loam) in order to study the effect of adding different types of nitrogen fertilizer (urea, di- ammonium phosphate and ammonium sulphate) at level 200 kgN ha-1. Zinc fertilizer has been sprayed with concentrations (0, 20, 40 and 60) mg ZNL-1 on growth and yield of snake cucumber. The results showed a significant increase in ammonium sulphate fertilizer in plant length, dry weight, leaf area, early yield, plant yield and total yield. The results showed that the concentration of 60 mg  L-1 was significantly higher in plant length, dry weight, early yield, plant yield and total yield.